Flexible Work Shift Policy, Burnout, and Performance among Hospital Administrative Staff: A Cross-Sectional Correlational Study - Jannah, Miftahul; Zebua, Arianus (Journal of Applied Nursing and Health, 2025)
Background: Flexible work shift policies are increasingly adopted to promote employee well-being and productivity. However, empirical evidence regarding their impact on burnout and job performance among non-medical hospital staff in Indonesia remains limited, creating a gap in understanding how such policies function in this context. This study aimed to analyse the effects of flexible work-shift policies on burnout and performance among administrative staff at Medan Adventist Hospital. Methods: A cross-sectional correlational design was used, following the STROBE reporting guideline, involving 50 administrative employees selected through saturated sampling. Instruments included the Flexible Work Shift Questionnaire, Maslach Burnout Inventory, and a performance questionnaire based on Robbins’ theory. All tools demonstrated acceptable validity and reliability. Data analysis employed Pearson correlation with a significance level of p < 0.05, accompanied by effect size (r²) calculations. Results: Flexible work shifts were negatively associated with burnout (r = –0.512, p = 0.001, r² = 0.26) and positively associated with performance (r = 0.628, p < 0.001, r² = 0.39). Burnout also showed a negative correlation with performance (r = –0.473, p = 0.002, r² = 0.22).. Conclusion: Flexible work shift policies significantly reduce burnout and enhance job performance. These findings highlight the value of structured, well-supervised flexibility as an evidence-based HR strategy that supports employee well-being and strengthens hospital operational quality.